The management of periprosthetic fractures Oxford trimodular femoral stem. A survivorship study. - Fawzy, E; de Steiger, R; Gundle, R; McLardy-Smith, P; Murray, D (2009)
A consecutive series of 40 periprosthetic femoral fractures, treated with revision hip surgery using the Oxford trimodular femoral stem, were retrospectively studied, with an average follow-up of 7.9 years. Fractures were classified according to the Vancouver classification. There were 5 type B1 fractures, 28 type B2, and 7 type C. Radiographic union was achieved in 38 (95%) hips. The mean time to fracture union was 3.5 months. The prosthesis survival at 5 years was 95% (confidence interval, 88%-100%). Clinical results were good with a mean Oxford hip score of 30 (hip score maximum, 48). Complications included 1 nonunion, 1 infection, 1 dislocation, and 2 aseptic loosening. The Oxford trimodular femoral component is a safe and reliable prosthesis for the treatment of periprosthetic femoral fractures with satisfactory medium-term results.